Partnering in offshore drilling projects. Issue 1 (4th January 2017) - Børve, Sjur; Ahola, Tuomas; Andersen, Bjorn; Aarseth, Wenche
Abstract : Purpose: The purpose of this paper is to evaluate to which extent partnering practices observed in earlier research focussing on the construction industry are applied in offshore development drilling projects. Design/methodology/approach: The paper reviews earlier research on project partnering and the relationship-based procurement (RBP) taxonomy. The taxonomy is then empirically applied to describe partnering practices in an incentive-based drilling project in Norway. Findings: Many elements of project partnering observed earlier in construction projects were found to characterize offshore development drilling projects. However, as assessed using the RBP framework, the authors found that partnering elements in observed context rated consistently lower than elements previously reported in the construction industry, indicating a lower maturity of partnering practices in the studied context. Practical implications: The present study provides a multi-dimensional and systematic description of partnering practices in offshore drilling projects. Project owners can utilize this information to identify partnering elements requiring particular emphasis when initiating and managing drilling projects. Based on the findings, such elements include transparency and open-book auditing, integrated risk mitigation and insurance practices and establishment of authentic leadership. The findings further imply that partnering models cannot be directly applied across industry boundaries but must be tailored to fit the salient characteristics of each context. Originality/value: The paper systematically describes to which extent specific partnering elements of the RBP taxonomy are applied in offshore drilling projects.